Goya : A Portrait of the Artist - Tomlinson, Janis A. (Book collections on Project MUSE., 2020)
"This biography, authored by one of the world's leading experts on Goya, makes available never-before translated documents of his life, and uses new research in Spanish, including detailed information on his youth, family, commissions, correspondence, and travels to create the most complete portrait yet of an often elusive artist and the dramatically changing society in which he lived and worked. Contrary to past projects that have portrayed Goya as an isolated figure, obsessed with darkness and death, Janis Tomlinson's deeply researched biography presents a painter convinced of his own genius and capacity for creation, one with an unrelenting drive, whose great sociability and skill in navigating court intrigues will come as a revelation to scholars and general readers alike"--